2021
DOI: 10.1371/journal.pcbi.1009108
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry and machine learning for the accurate diagnosis of benzylpenicillin and multidrug resistance of Staphylococcus aureus in bovine mastitis

Abstract: Staphylococcus aureus is a serious human and animal pathogen threat exhibiting extraordinary capacity for acquiring new antibiotic resistance traits in the pathogen population worldwide. The development of fast, affordable and effective diagnostic solutions capable of discriminating between antibiotic-resistant and susceptible S. aureus strains would be of huge benefit for effective disease detection and treatment. Here we develop a diagnostics solution that uses Matrix-Assisted Laser Desorption/Ionisation–Tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…Next, we introduced a novel, yet simple method called dynamic binning to extract features from the preprocessed spectra. Dynamic binning addresses the shortcomings of two commonly used feature engineering methods for MALDI-TOF MS data: peak detection (i.e., using intensity peaks as features) [13, 15, 18], and fixed-length binning (i.e., using bins of pre-specified size as features) [14, 17]. The former approach requires additional analysis steps for peak alignment and potentially overlooks regions without peaks, while the latter approach often generates a large feature set that greatly outnumbers sample size, thereby increasing the chances of over-fitting.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we introduced a novel, yet simple method called dynamic binning to extract features from the preprocessed spectra. Dynamic binning addresses the shortcomings of two commonly used feature engineering methods for MALDI-TOF MS data: peak detection (i.e., using intensity peaks as features) [13, 15, 18], and fixed-length binning (i.e., using bins of pre-specified size as features) [14, 17]. The former approach requires additional analysis steps for peak alignment and potentially overlooks regions without peaks, while the latter approach often generates a large feature set that greatly outnumbers sample size, thereby increasing the chances of over-fitting.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study by Tang and colleagues ( 41 ) reported that MALDI-TOF MS on intact bacteria combined with a refined analysis framework allows accurate classification of methicillin-sensitive Staphylococcus aureus (MSSA) and MRSA. Esener and colleagues showed that MALDI-TOF has a sensitivity of 99.93% ± 0.25%, specificity of 95.04% ± 3.83%, and accuracy = 97.54% ± 1.91% ( 42 ). MALDI-TOF is low in cost, and analysis can be conducted within a short time, allowing rapid microbial resistance to be detected.…”
Section: Resultsmentioning
confidence: 99%
“…SVM achieved 91.66% accuracy in identifying two groups of samples based on seven features, and the authors proposed biomarkers that play a role in pathogenesis, such as the metabolism of nicotinamide and glutathione as well as tryptophan and sphingolipids. In another recent study, SVM was used to classify benzylpenicillin and multidrug resistance in Staphylococcus aureus [ 54 ]. The authors performed matrix-assisted laser desorption/ionization–time of flight mass spectrometry to identify signature profiles of antibiotic resistance in S. aureus isolates.…”
Section: Application Of Machine Learning For the Diagnosis Of Diseasesmentioning
confidence: 99%